(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Surgical Site Infections (SSIs) remain a significant challenge in healthcare settings, contributing to increased morbidity, prolonged hospital stays, and higher treatment costs. Nurses play a critical role in preventing SSIs through adherence to infection control measures, yet gaps in knowledge, attitudes, and practices (KAP) continue to hinder effective prevention strategies. Educational interventions have been recognized as essential tools for enhancing nurses’ competencies in SSI prevention, improving adherence to best practices, and reducing infection rates. However, the effectiveness of such programs in improving nurses’ KAP requires further investigation to optimize infection control efforts. Objective: This study aims to assess nurses’ knowledge, attitudes, and practices related to SSI prevention and evaluate the impact of an educational intervention program on improving their competencies. Specifically, the research investigates existing gaps in knowledge and adherence to best practices, examines nurses’ perceptions of SSI prevention strategies, and measures the effectiveness of targeted training in enhancing infection control compliance. Methodology: A cross-sectional study design was employed using a structured questionnaire distributed to nurses working in surgical wards, operating rooms, and postoperative care units. The questionnaire covered key areas, including nurses’ baseline knowledge of SSI risk factors, their attitudes toward infection prevention, and their current practices in surgical settings. Following the initial assessment, an educational intervention was implemented, comprising lecture sessions, hands-on training, and case-based discussions on SSI prevention protocols. Post-training evaluations were conducted to measure improvements in KAP. Data were analyzed using descriptive and inferential statistical methods to assess the effectiveness of the intervention. Key Findings: The study findings indicate that while a majority of nurses demonstrated moderate awareness of SSI prevention guidelines, significant gaps existed in certain critical areas, including proper wound care techniques, surgical hand hygiene compliance, and appropriate antibiotic prophylaxis administration. Nurses’ attitudes toward SSI prevention were generally positive; however, a lack of confidence in certain infection control measures was observed. Post-intervention results revealed a substantial improvement in knowledge scores, increased adherence to evidence-based practices, and greater confidence in implementing infection control measures. The educational program was particularly effective in reinforcing hand hygiene compliance, sterile technique adherence, and early recognition of SSI symptoms. Future Directions: To sustain the benefits of educational interventions, healthcare institutions should integrate continuous professional development programs focused on SSI prevention. Future research should explore the long-term impact of such training on clinical outcomes, assess the role of digital learning platforms in reinforcing infection control education, and investigate the effectiveness of interdisciplinary training approaches involving surgeons, nurses, and infection control specialists. Additionally, institutional policies should prioritize ongoing infection prevention audits, mentorship programs, and resource allocation to enhance nurses’ adherence to SSI prevention protocols. Conclusion: This study underscores the critical role of educational interventions in improving nurses’ knowledge, attitudes, and practices regarding SSI prevention. By addressing existing knowledge gaps and reinforcing best practices, structured training programs can significantly enhance infection control measures in surgical settings. Sustained efforts in nurse education, institutional support, and continuous professional development are essential for reducing SSI rates and improving patient safety in healthcare environments.